Anxiolytic effect of the extract from Rhaponticum uniflorum roots - N. K. Tatarinova (Scientific Сentre for Family Health and Human Reproduction Problems, 2015)
The experiments were carried out on white Wistar rats. The dry extract from Rhaponticum uniflorum L. roots was administered to the animals at the doses of 200 and 300 mg/kg for 7 days before testing. The behavior of animals was observed with the use of the tests "elevated plus maze" (EPM) and "dark/ light chamber". Under the influence of the extract from Rhaponticum uniflorum L. at the doses of 100, 150 and 250 mg/kg the number of entries into the open branch of EPM rises to 2,0-3,0 times and staying period in them rises 3,1-4,1 times in comparison with the control. The test "dark/light chamber" has shown that the number of entries of the experimental animals into the light bay of the "dark/light chamber" and the period of staying in it is 2,0 times increased.